A262 COLONIC MUCOSA-ASSOCIATED LYMPHOID TISSUE (MALT) LYMPHOMA, A RARE OCCURENCE: A LITERATURE REVIEW AND CASE SERIES. (1st March 2018) - Chan, M; Rostom, A; Faught, C; Dube, C
Abstract: Background: Extranodal mucosa-associated lymphoid tissue (MALT) lymphoma is a clonal B-cell neoplasm that develops in the marginal zone of lymphoid follicles. They make up about 5% of all non-Hodgkin's lymphomas. The most common extranodal site for MALT lymphomas is the stomach, followed by the small bowel. Colonic MALT lymphomas are rare and, as a result, there are no guidelines for the workup and management of these lymphomas. Aims: This case series aims to review the literature of existing cases of colonic MALT lymphoma and to share our experience with diagnosis, workup and management of colonic MALT lymphoma. Methods: A literature search was conducted using an advanced PUBMED search. Charts of 4 identified cases diagnosed in 2016 - 2017 were reviewed. Results: A literature review of colonic MALT lymphomas revealed a few dozen cases, either isolated or in conjunction with MALT in the upper GI tract. Presenting symptoms included abdominal pain, gastrointestinal bleeding, positive fecal occult blood test and weight loss. Workup included colonoscopy and biopsy, endoscopic assessment of the upper GI tract to assess for other foci of MALT lymphoma as well as testing for Helicobacter pylori and celiac testing, which have both been associated with gastric MALT lymphomas. Endoscopically they can appear as a polyp or mass with a smooth surface with changes in vascular pattern, but can be ulcerated if more advanced. The management of colonic MALT lymphoma varies. Patients with limited disease were often treated with radiotherapy, surgical resection or endoscopic resection via endoscopic mucosal resection or endoscopic submucosal dissection. Patients with multiple foci of disease or lymph node involvement were usually treated with chemotherapy and/or rituximab. There have been reports of resolution of the colonic MALT lymphoma after H. pylori treatment, even in patients who were H. pylori negative. We present our experience with the diagnosis and management of 4 cases of colonic MALT lymphoma. This includes cases of asymptomatic colonic MALT lymphoma diagnosed on routine colonoscopy which were treated conservatively with close monitoring, and a case with a concurrent gastrointestinal stromal tumor (GIST) in the stomach. In the latter case, the MALT lymphoma was treated with chemotherapy and rituximab with good response, and the GIST was surgically resected. Conclusions: Colonic MALT lymphomas are considered to be rare; however, the diagnosis of 4 cases at our institution in the last 2 years would suggest otherwise. Therefore, endoscopists should be familiar with this condition and its endoscopic features. Patients with asymptomatic, limited stage colonic MALT lymphoma can be managed conservatively. Although we report one case of colonic MALT lymphoma occurring concurrently with a gastric GIST, there is no clear association between the two conditions. Funding Agencies: None